Personality and Substance Use: Psychometric Evaluation and Validation of the Substance Use Risk Profile Scale (SURPS) in English, Irish, French, and German Adolescents. (14th October 2015) - Jurk, Sarah; Kuitunen‐Paul, Sören; Kroemer, Nils B.; Artiges, Eric; Banaschewski, Tobias; Bokde, Arun L. W.; Büchel, Christian; Conrod, Patricia; Fauth‐Bühler, Mira; Flor, Herta; Frouin, Vincent; Gallinat, Jürgen; et al.
Abstract : Background: The aim of the present longitudinal study was the psychometric evaluation of the Substance Use Risk Profile Scale (SURPS). Methods: We analyzed data from N = 2, 022 adolescents aged 13 to 15 at baseline assessment and 2 years later (mean interval 2.11 years). Missing data at follow‐up were imputed ( N = 522). Psychometric properties of the SURPS were analyzed using confirmatory factor analysis. We examined structural as well as convergent validity with other personality measurements and drinking motives, and predictive validity for substance use at follow‐up. Results: The hypothesized 4‐factorial structure (i.e., anxiety sensitivity, hopelessness, impulsivity [IMP], and sensation seeking [SS]) based on all 23 items resulted in acceptable fit to empirical data, acceptable internal consistencies, low to moderate test–retest reliability coefficients, as well as evidence for factorial and convergent validity. The proposed factor structure was stable for both males and females and, to lesser degree, across languages. However, only the SS and the IMP subscales of the SURPS predicted substance use outcomes at 16 years of age. Conclusions: The SURPS is unique in its specific assessment of traits related to substance use disorders as well as the resulting shortened administration time. Test–retest reliability was low to moderate and comparable to other personality scales. However, its relation to future substance use was limited to the SS and IMP subscales, which may be due to the relatively low‐risk substance use pattern in the present sample.